Evidence of Poor Bottom Water Ventilation during LGM in the Equatorial Indian Ocean - Chandana, K. R.; Bhushan, Ravi; Jull, A. J. T. (Frontiers in Earth Science, 2017)
Multi-proxy approach for the reconstruction of paleo-redox conditions is attempted in a radiocarbon (14C) dated sediment core near the equatorial Indian Ocean. Based on behavior and distribution of redox sensitive and productivity proxies, the study demonstrates prevalence of anoxic bottom water conditions during LGM due to poorly ventilated bottom waters augmented by high surface productivity resulting in better preservation of organic carbon (OC). During early Holocene, the equatorial Indian Ocean witnessed high sedimentation rates resulting in high organic carbon (OC) with depleted redox sensitive element thereby causing better preservation of OC. The study underscores poor bottom water ventilation during LGM and preservation of OC as a result of high sedimentation rate in early Holocene.